Pengaruh Kompetensi Profesional Guru, Literasi Digital dan Fasilitas Olahraga terhadap Proses Pembelajaran Efektif Mata Pelajaran Pendididikan Jasmani, Olahraga dan Kesehatan - Chaeruddin, Awal; Sulaiman, Sulaiman; Irawan, Fajar Awang (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This study aims to analyze the influence of teachers' professional competence, digital literacy, and sports facilities on the effective learning process. The research method used in this study is a causal associative method and uses a quantitative approach. The data collection technique was carried out by questionnaire and observation methods. Data and data sources are obtained from primary and secondary data. Primary data was obtained from a sample of 285 students from all students of MANU Putra, MANU Putri, and SMK PK Mekanika Buntet Pesantren Cirebon. Secondary data was obtained from the data from quantitative descriptive analysis. The results of this study found that the average professional competence of teachers was 32.93. The average digital literacy is 39.61. The average sports facilities (including facilities and infrastructure) was 3.19. The average learning effectiveness was 33.75. Therefore, it can be concluded that teachers' professional competence, digital literacy, and sports facilities have a positive and significant effect on the effective learning process of physical education, sports and health subjects with a total influence of 59.1% while the rest are influenced by other variables that are not studied. Of the three variables developed, Digital Literacy (X2) has the largest contribution, the next is Teacher Professional Competence (X1) and finally the Sports Facilities variable (X3). However, the increase in influence will be greater if the implementation is moderated with better management efforts. Conclusion: The Professional Competence of PJOK Teachers at MANU Putra, MANU Putri, and SMK PK Mekanika Buntet Pesantren Cirebon has a positive and significant impact on the Effective Learning Process at MANU Putra, MANU Putri, and SMK PK Mekanika Buntet Pesantren Cirebon. This means that the higher the professional competence of the teachers, the more effective the sports learning process experienced by students, and the teachers are competent to develop learning that can lead students to achieve better results. Keywords: Digital, Effective, Professional